Long-Term Monitoring of In-Water Abundance of Juvenile Pelagic Loggerhead Sea Turtles (Caretta caretta): Population Trends in Relation to North Atlantic Oscillation and Nesting - Dellinger, Thomas; Zekovic, Vladimir; Radeta, Marko (Frontiers in Marine Science, 2022)
Sea turtles have various life-stages, typically being oceanic foragers as juveniles while shifting to more coastal habitats as they mature. The present study focuses on the least studied and well known of these, the juvenile oceanic life stage for the loggerhead sea turtle, Caretta caretta. Loggerhead sea turtles remain threatened by fisheries and their distribution and habitat change in the North Atlantic remains poorly understood. After hatching and swimming out to sea, turtles spend 7 or more years in the pelagic life stage. Madeira Island has an advantage of being situated in the middle of the North Atlantic developmental habitat for loggerheads originating both from the US, as well as, from Cape Verde and other mixed source rookeries. Understanding the demographics of this oceanic life stage has been described as a research priority. We here present a population trendline and the abundance variation of oceanic stage loggerheads, measured at a single geographic spot in Madeiran waters, over the period of 15 years. We find that the observed loggerhead distribution results from combined effects of physical and biological processes within the North Atlantic. We explore physical phenomena that influence abundance variability, and find that oscillations in climate affect the turtle migrations, as does the population recruitment from the nesting rookeries. For this, we use novel cost-effective census methods that take advantage of platforms of opportunity from the blue ecotourism industry. To study the time series and their correlations we use spectral analysis, a method not commonly used in traditional population assessments, including Wavelet and Fourier Transformations (WT and FFT), and Digital Signal Processing (DSP) techniques. A strong anti-correlation between sea turtle sightings and North Atlantic Oscillation seasonal components was found, which implies that loggerhead sea turtles are less abundant during positive NAO phases. We also detected long period trends in the sighting data which we relate to La Nina and El Ninno oscillations. Source rookeries also influenced the sighting data with a time-lag of 7 years, which coincides with the average time that turtles spend as oceanic juveniles.